MEKANISME ASSESMEN TERPADU TERHADAP REHABILITASI KORBAN PENYALAHGUNAAN NARKOTIKA DITINJAU DARI PERSPEKTIF UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Marpaung David; Tatok Sudjiarto; Armunanto Hutahaean (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this research is to know and analyse the assessment arrangements for rehabilitation in rehabilitating victims of narcotics abuse and to know and analyse what rehabilitation obligations for narcotics abuse are based on the perspective of Law Number 35 of 2009 concerning Narcotics. The method that is used in this research is qualitative research, which is a research procedure that produces descriptive data in the form of written or spoken words from people and behaviour that can be observed. In addition, primary, secondary and tertiary data are also used. The result of this research is that the integrated assessment mechanism for the rehabilitation of victims of drug abuse is appropriate. However, there are shortcomings in the verdict imposed by the judge on the defendant. Where in the verdict the judge did not impose sanctions in the form of social rehabilitation and medical rehabilitation which should be required for drug abusers.